2018
DOI: 10.1161/circresaha.117.312536
|View full text |Cite
|
Sign up to set email alerts
|

Stress Signaling JNK2 Crosstalk With CaMKII Underlies Enhanced Atrial Arrhythmogenesis

Abstract: We have identified JNK2-driven CaMKII activation as a novel mode of kinase crosstalk and a causal factor in atrial arrhythmic remodeling, making JNK2 a compelling new therapeutic target for AF prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 52 publications
1
46
0
Order By: Relevance
“…Cooper et al (2013) also demonstrated that, in the presence of β-adrenergic agonist isoproterenol, RyR2 phosphorylation at CaMKII site Serine-2814 was significantly increased in ventricular myocytes from old rabbit hearts (four to six years old) in comparison to young (five to nine months old) [9]. A significantly increased activity of stress response kinase JNK2 was reported to activate CaMKII and, thus, upregulate RyR2-mediated diastolic SR Ca 2+ leak in aged mouse atria (24–32 months old) [39]. Guo et al (2014) observed increased RyR2 phosphorylation at CaMKII-specific site S2814 in aged mouse atrial myocytes, which increased aberrant intracellular waves and facilitated AF initiation [40].…”
Section: Intracellular Ca2+ Homeostasis In the Aged Heartmentioning
confidence: 99%
“…Cooper et al (2013) also demonstrated that, in the presence of β-adrenergic agonist isoproterenol, RyR2 phosphorylation at CaMKII site Serine-2814 was significantly increased in ventricular myocytes from old rabbit hearts (four to six years old) in comparison to young (five to nine months old) [9]. A significantly increased activity of stress response kinase JNK2 was reported to activate CaMKII and, thus, upregulate RyR2-mediated diastolic SR Ca 2+ leak in aged mouse atria (24–32 months old) [39]. Guo et al (2014) observed increased RyR2 phosphorylation at CaMKII-specific site S2814 in aged mouse atrial myocytes, which increased aberrant intracellular waves and facilitated AF initiation [40].…”
Section: Intracellular Ca2+ Homeostasis In the Aged Heartmentioning
confidence: 99%
“…Concerning AF, the cardiomyocyte sleeves overlapping the pulmonary veins along with Ca 2+ handling disorders are the sources of the ectopic electrical activity, while re-entry circuits are promoted by the atrial tissue heterogeneity and disorders in the intercellular electrical coupling mediated by connexin (Cx) channels [3,5,8,9,[30][31][32][33][34]. The association of AF with the atrial Cx37 and Cx40 gene polymorphisms [35], as well as somatic mutations in GJA5 (encoding Cx40), have been identified in AF [36,37].…”
Section: A Short Overview On Afmentioning
confidence: 99%
“…Though this discussion of potential pharmacological targets is certainly not exhaustive, a final therapeutic intervention involves c-Jun N-terminal kinase, or JNK. This kinase, responsible for the activation of CaMKII, is a factor in the development of atrial arrhythmias [ 143 ]. Left unchecked, this pathway results in the disturbance of diastolic calcium handling, as mentioned earlier in the review [ 143 , 144 ].…”
Section: Dietary and Pharmacological Interventionsmentioning
confidence: 99%
“…This kinase, responsible for the activation of CaMKII, is a factor in the development of atrial arrhythmias [ 143 ]. Left unchecked, this pathway results in the disturbance of diastolic calcium handling, as mentioned earlier in the review [ 143 , 144 ]. Targeted inhibition of JNK could be yet another mechanism for combatting the oxidative stress and pro-arrhythmogenic effects of a chronic HFD.…”
Section: Dietary and Pharmacological Interventionsmentioning
confidence: 99%